Analisis Pengaruh Orientasi Kewirausahaan dan Kemampuan Manajemen Terhadap Strategi Pemasaran Serta Dampaknya Terhadap Kinerja Usaha Kecil Manufaktur Di Magetan - Rian Histiarini, Aprisa, Drs. M. Farid Wajdi, MM., Ph.D, Dr. Anton Agus Setyawan, SE.,MSi (2016)
The development of small and medium enterprises in Indonesia is growing rapidly but there are still many problems encountered. This problem is suspected because many owners don't have entrepreneruial orientation, management skills and the right marketing strategies in their business. The owners and managers of small businesses required to more understanding the market conditions and passion of consumers because of high competition in business. This study has intention to determine the relationship between entrepreneurial orientation, management skills and marketing strategies to increase business performance. This research was conducted by distributing questionnaires on small businesses of manufacturing industry in Magetan. The number of respondents who researched is 96 including the owners or managers of manufacturing small businesses in Magetan. For analyzing and interpreting data using Partial Least Square (PLS). The finding from study indicated that the entrepreneurial orientation and management skills have positive and significant impact on marketing strategy. Entrepreneurial orientation and management skills impact on performance of small businesses when mediated by marketing strategies. Result also reveal that management skills and marketing strategies has directly impact on performance of a small business.